The identification and analytical characterization of 2, 2′‐difluorofentanyl. Issue 4 (2nd October 2017) - Liu, Cuimei; Li, Tao; Han, Yu; Hua, Zhendong; Jia, Wei; Qian, Zhenhua
Abstract: New psychoactive substances (NPS) have expanded their distribution and become widely available in the global market in recent years. The illicit use of fentanyl and its analogs has become an important worldwide concern linked to their high potency and risk of fatal overdose. This study describes the analytical characterization of a new fentanyl derivative N ‐(1‐(2‐fluorophenethyl)‐4‐piperidinyl)‐ N ‐(2‐fluorophenyl)propionamide (2, 2′‐difluorofentanyl). Identification was based on ultra‐high‐performance liquid chromatography–quadrupole time‐of‐flight–mass spectrometry (UHPLC–QTOF–MS), gas chromatography–mass spectrometry (GC–MS), Fourier transform infrared (FTIR) spectroscopy, and nuclear magnetic resonance (NMR) spectroscopy. To our knowledge, this study is the first to report on analytical data for this compound. The most abundant fragment ion in the electrospray ionization (ESI) mass spectrum under collision‐induced dissociation (CID) mode was formed by the cleavage between the piperidine ring and the N ‐phenyl‐amide moiety of the protonated molecule. Two diagnostic ions in the electron ionization (EI) mass spectrum were formed by the loss of a tropylium ion (M‐91), and by the degradation of the piperidine ring and dissociate of the COC2 H5 moiety altogether, respectively. Abstract : A fentanyl derivative N ‐(1‐(2‐fluorophenethyl)piperidin‐4‐yl)‐ N ‐(2‐fluorophenyl)propionamide (2, 2′‐difluorofentanyl) was identified using UHPLC–QTOF–MS, GC–MS, FTIR, and NMR.